Chances and limitations of a low-cost mobile 3D scanner for breast imaging in comparison to an established 3D photogrammetric system. Issue 10 (October 2018) - Koban, Konstantin C.; Härtnagl, Felix; Titze, Virginia; Schenck, Thilo L.; Giunta, Riccardo E.
Summary: Background: In search of new possibilities in 3D surface imaging, several nonmedical scanning systems have been assessed for their implementation in plastic surgery. The aim of this study was to compare a new affordable 3D imaging consumer product with an established medical 3D imaging system for objective 3D breast imaging. Method: We compared a low-cost mobile, handheld scanner against an established medical 3D surface imaging system. Forty-two female patients who underwent different types of breast surgery were captured in a 3D view with both devices. Digital breast measurement, volume measurement, and breast surface-to-surface analysis were done using Mirror software. Repeatability was assessed by repeated 3D scans of the torso and surface-to-surface analysis. Results: Digital breast measurement showed low differences with good-to-excellent correlation between both devices. Mean breast volume difference was small (−5.11 ± 32.10 mL) within the 95% limits of agreement. Surface-to-surface analysis yielded a higher surface deviation in the lower breast quadrants (1.62 ± 0.80 mm root mean square [RMS] error and 1.81 ± 0.88 mm RMS error) than in the upper breast quadrants. Repeatability was satisfactory with a mean of 0.636 ± 0.279 mm RMS error. Conclusion: Affordable mobile surface scanners may offer new perspectives in the future for 3D breast imaging. Although surface acquisition was sufficient for breast measurements in comparison to an established system, the lack of appropriate medical software for patient consultation next to moderate texture quality needs to be improved for wider acceptance in plastic surgery.